Work Safety and Health Principles (K3) in the Design of Workshop Center of Artificial Natural Stone in Gianyar, Bali - Digjaya Putra, A. A. Gde Dwika; Paramadhyaksa, I Nyoman Widya; Bupala, Ida Bagus Ngurah (Journal of A Sustainable Global South; Vol 1 No 2 (2017): August 2017DO - 10.24843/jsgs.2017.v01.i02.p03, 2017)
The embodiment of Balinese buildings is known to be synonymous with the use of natural stone materials which are exposed in such a way and not given additional dyes/coatings. The material used is usually in the form of bricks and sandstone. The center of the natural stone craftsman is a location of concentration of craftsmen who produce hand-crafted natural stone. The artificial natural stone craftsman center has a workshop used by artisans to produce crafts. In the production process, there is certainly a risk of workplace accidents that can be experienced by craftsmen. At the center must implement occupational safety and health to provide a sense of security and comfort in work. There are many work accidents caused by human factors, workplace accidents must be avoided so that the production of crafts can run smoothly. The risk of workplace accidents that can occur in craftsmen centers in the form of being injured by sharp objects, being hit by a hammer, or falling. The health of craftsmen is also an important factor in the production of artificial natural stones. Healthy craftsmen will be able to work productively and produce good quality craft items. The application of occupational safety and health is expected to be a solution in reducing the risk of workplace accidents that can occur in the production process. Index Terms — centers, craftsmen, accidents, health.